1993
DOI: 10.1093/ejo/15.4.249
|View full text |Cite
|
Sign up to set email alerts
|

The initial phase of orthodontic root resorption incident to local compression of the periodontal ligament

Abstract: The present light microscopic investigation was undertaken in order to study the initial phase of orthodontic root resorption in areas of pressure and, more specifically, to focus on the first cells that penetrate the root surface. Twenty-one upper first molars (rats) and 31 lower first molars (mice) were moved mesially by a fixed orthodontic appliance. The experimental periods were 1, 2, 3, 4, and 5 days in rats, and 1, 2, 3, 4, 5, 6, 7, and 8 days in mice. Tartrate-resistant acid phosphatase (TRAP) and Haema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
13

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 0 publications
3
93
0
13
Order By: Relevance
“…An inefficient acute phase response leads to an exacerbated macrophage infiltration, with slow resolution of necrotic hyalinization and and excessive tissue damage, characterized by root resorption. The association of macrophages with root resorption has been reported previously, (Brudvik & Rygh, 1993a;Brudvik & Rygh, 1993b;Brudvik & Rygh, 1994a;Brudvik & Rygh, 1994b;Roberts et al, 1981) but the role of neutrophils has been overlooked. A very interesting contrast in the orthodontic catabolic process in the KO is that more root resorption was observed, but not more bone resorption away from the PDL-bone interface.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…An inefficient acute phase response leads to an exacerbated macrophage infiltration, with slow resolution of necrotic hyalinization and and excessive tissue damage, characterized by root resorption. The association of macrophages with root resorption has been reported previously, (Brudvik & Rygh, 1993a;Brudvik & Rygh, 1993b;Brudvik & Rygh, 1994a;Brudvik & Rygh, 1994b;Roberts et al, 1981) but the role of neutrophils has been overlooked. A very interesting contrast in the orthodontic catabolic process in the KO is that more root resorption was observed, but not more bone resorption away from the PDL-bone interface.…”
Section: Discussionmentioning
confidence: 74%
“…Orthodontic tooth movement involves two fundamental processes possibly mediated by P2X7R: the metabolism of an associated necrotic-type tissue (hyalinized periodontal ligament tissue) and bone modeling/remodeling (Reitan, 1994;Roberts, 2005;Roberts et al, 1981;Rygh, 1974;Rygh, 1976). External root resorption, an undesirable side effect of tooth movement, has been associated with the presence of macrophages, possibly linking it to a chronic inflammatory response (Brudvik & Rygh, 1993a;Brudvik & Rygh, 1993b;Brudvik & Rygh, 1994a;Brudvik & Rygh, 1994b;Rygh, 1974;Rygh, 1976;Saito et al, 1991a). A strong association has been reported between IL-1 beta and root resorption Al-Qawasmi et al, 2003a).…”
Section: Development Of Biomechanical Orthodontic Models Introductionmentioning
confidence: 99%
“…2 Thus, it is a plausible assumption that apical root displacement (ARD) is directly associated with ARR since more ARD involves resorption of a larger amount of hyalinized tissue. However, most previous studies have found only marginally significant correlations between the amount of ARD and ARR of maxillary incisors.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Radiographic, two dimensional, evaluation studies were limited to measuring only the amount of root apex loss and were highly inaccurate because of the magnification error and low reproducibility. 14 …”
Section: Introductionmentioning
confidence: 99%